The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11250-022-03356-8
|View full text |Cite
|
Sign up to set email alerts
|

Research on acute phase proteins and inflammatory cytokines biomarkers in dromedary camels (Camelus dromedarius) with clinical endometritis

Abstract: Uterine diseases are prevalent in she-camel and lead to economic losses because of decreased fertility.The aim of this study is to look into the expression pattern of acute-phase proteins (APPs) and in ammatory cytokines in dromedary camels with clinical endometritis (CE) to highlight their role in immune-pathogenesis of the disease. Moreover, to identify the use of these parameters as a complementary tool for CE screening as well as investigate the e cacy of ceftiofur antibiotic. APPs and in ammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, a considerable elevation in SOD levels was observed after treatment when compared to both control and diseased cows. Results in this study are consistent with those observed in previous studies noting a decrease in SOD in she‐camels with uterine infection (El‐Deeb et al., 2022b; El‐Deeb, Iacob, et al., 2022). SOD is an antioxidant enzyme that plays a crucial role in the defence against OS (He et al., 2017; Wang et al., 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, a considerable elevation in SOD levels was observed after treatment when compared to both control and diseased cows. Results in this study are consistent with those observed in previous studies noting a decrease in SOD in she‐camels with uterine infection (El‐Deeb et al., 2022b; El‐Deeb, Iacob, et al., 2022). SOD is an antioxidant enzyme that plays a crucial role in the defence against OS (He et al., 2017; Wang et al., 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the decrease in SOD levels may contribute to the development of tissue damage and sepsis in cows with pyometra. Decreased serum levels of SOD have been found to be a reliable indicator of disease progression and treatment response in several studies (El‐Deeb et al., 2022b; El‐Deeb, Iacob, et al., 2022). However, it is essential to consider the limitations and potential confounding factors of SOD levels when interpreting results in clinical practice.…”
Section: Discussionmentioning
confidence: 99%